Mothers's Knowledge and Behavior of Anemia Prevention in Children: Application of Pender's Health Promotion Model - Ni Kadek Dwi Anjani; Byba Melda Suhita; Yenny Puspitasari; Sri Kardjati (Journal for Quality in Public Health, 2020)
Prevalence of anemia in children in Indonesia is still quite high. Parents' behavior in preventing anemia in children is still lacking. Health promotion model (HPM) with a Pender's model is needed. This study was aimed to develop a model of health promotion with a Pender theory approach to maternal behavior on the prevention of childhood anemia. Quasi Experiment with Pre and Post Test design was conducted in Kubutambahan II Primary Health Care. Data was collected in 100 respondents and analyzed by Mc Nemar test. The results showed there was an effect of health promotion on mother's knowledge of anemia prevention (p = 0,000). There was no effect of health promotion on mother's attitudes of anemia prevention (p = 0.845). There is an effect of health promotion on the actions/behavior of mothers regarding the prevention of anemia in children (p = 0,000). The developing health promotion based on the HPM approach can increase knowledge and behavior about preventing anemia. Health promotion by conducting outreach to the community needs to be carried out continuously by involving all aspects such as health workers, community leaders, community health workers and families to improve community health status.